2021
DOI: 10.1097/md.0000000000027538
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase to albumin ratio as a prognostic factor for patients with severe infection requiring intensive care

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Although any analysis of LAR has not yet been reported in the current emergency hernia surgery literature, its value was previously demonstrated as a parameter that affected mortality in severe infections requiring intensive care. [26] Other indices were also shown to associate with either disease diagnosis, clinical outcomes, morbidity, or mortality in various previous studies, such as the NPR in cardiac emergencies, IBil/Albumin in neurological and neonatal emergencies, LDH/WBC in systemic inflammation and the prognosis of Coronavirus disease-19, PAR in cancers of especially the hepatobiliary system, and NAR in sepsis and septic shock. [27][28][29][30][31][32] The results of the present study revealed that among the indices commonly used as indicators of systemic inflammation in various diseases LDH/WBC, NPR and NAR were significantly associated with strangulation in emergency anterior abdominal wall hernias.…”
Section: Discussionmentioning
confidence: 92%
“…Although any analysis of LAR has not yet been reported in the current emergency hernia surgery literature, its value was previously demonstrated as a parameter that affected mortality in severe infections requiring intensive care. [26] Other indices were also shown to associate with either disease diagnosis, clinical outcomes, morbidity, or mortality in various previous studies, such as the NPR in cardiac emergencies, IBil/Albumin in neurological and neonatal emergencies, LDH/WBC in systemic inflammation and the prognosis of Coronavirus disease-19, PAR in cancers of especially the hepatobiliary system, and NAR in sepsis and septic shock. [27][28][29][30][31][32] The results of the present study revealed that among the indices commonly used as indicators of systemic inflammation in various diseases LDH/WBC, NPR and NAR were significantly associated with strangulation in emergency anterior abdominal wall hernias.…”
Section: Discussionmentioning
confidence: 92%
“…LDH is a valuable factor in determining the severity of infection. 30 Therefore, elevated LDH and CRP levels would be reliable alarm signals to note severe AU induced by infection. Moreover, as a supporter of aerobic glucose metabolism, LDH elevation marked the degree of T-cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it has been demonstrated that the LDH/albumin ratio independently affects mortality in severe infections requiring intensive care [ 19 ] and stroke-related pneumonia [ 22 ] in lower respiratory tract infections. [ 23 ] High LDH levels are an interesting biomarker associated with poor outcomes in patients with previous viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Several studies have used the LDH/albumin ratio as a prognostic factor in pneumonia patients. [19] Patients hospitalized with COVID-19 need regular monitoring of vital signs and, where possible, early recognition of the deteriorating patient and biomarkers that predict prognosis. The present study was designed to confirm whether LDH/albumin ratio can be used as an independent prognostic factor in patients with severe ARDS due to COVID-19.…”
Section: Introductionmentioning
confidence: 99%